The application of grey statistical method and analytic hierarchy process in the evaluation of community park rehabilitation landscapes - Qingtao Cheng; Qiuping Li (Humanities & Social Sciences Communications)
Abstract The rehabilitation landscape of community parks plays a significant role in the physical and mental health of urban residents, social interaction, improvement of the ecological environment, and the sustainable development of cities. This research applies the Grey Statistical Technique (GST) combined with the Analytic Hierarchy Process (AHP) model to establish an evaluation system for landscape assessment. The system is constructed based on three dimensions: physical rehabilitation, psychological rehabilitation, and spiritual rehabilitation. The GST method is utilized to screen and select evaluation indicators, while the AHP method is employed to construct the landscape evaluation system and calculate the weights of each indicator. The results are as follows: (1) Out of the 30 indicator factors, 13 were not selected through the GST method. (2) The weights of the criteria layer, from highest to lowest, are as follows: physical rehabilitation (D1) with a weight of 0.6370, psychological rehabilitation (D2) with a weight of 0.2583, and spiritual rehabilitation (D3) with a weight of 0.1047. (3) The highest and lowest values in the indicator layer are as follows: D1 (P14: illumination duration 0.2359, P17: hydrological conditions 0.0197); D2 (P21: sense of security 0.1433, P23: human-environment interaction 0.0162); D3 (P34: sense of pleasure 0.0400, P36: aesthetic value 0.0045). This research reduces the subjectivity in the evaluation indicators and provides valuable guidance for the design of rehabilitation landscapes in community parks.